Evaluasi Kesesuaian Peraturan Lkpp No. 12 Tahun 2021 Terhadap UU Administrasi Pemerintahan No. 30 Tahun 2014 - Peto Syamsul Alam (Riviera Publishing, 2026)
Government procurement is a strategic instrument in delivering public services and managing state finances, and therefore must be conducted in accordance with legal certainty, accountability, and the General Principles of Good Governance (Asas-Asas Umum Pemerintahan yang Baik/AUPB). Regulation of the National Public Procurement Agency Number 12 of 2021 (Perlem LKPP 12/2021) was enacted as a technical guideline for procurement through providers; however, its implementation raises several normative issues when examined in relation to Law Number 30 of 2014 on Government Administration (UU AP). This article aims to evaluate the compatibility of Perlem LKPP 12/2021 with the objectives and principles stipulated in UU AP 30/2014, to identify regulatory provisions that potentially create normative inconsistencies, and to propose recommendations for strengthening procurement governance. This study employs a normative juridical method using statutory, conceptual, and norm-mapping approaches. The findings indicate that several provisions of Perlem LKPP 12/2021—such as the authority of the Budget User Authority (KPA) as the final decision-maker in appeal objections, the obligation to submit a bid appeal guarantee amounting to 1% of the estimated contract value, ambiguous and multi-interpretable norms, non-affirmative advance payment arrangements for small enterprises, and one-sided performance evaluations of providers—are potentially inconsistent with the principles of legal certainty, prohibition of abuse of power, and legal protection as mandated by UU AP 30/2014. This article underscores the necessity of regulatory harmonization to ensure that technical procurement regulations do not exceed delegated authority, uphold legal protection, and promote fair, transparent, and accountable government procurement governance.